2019
DOI: 10.3892/ol.2019.11141
|View full text |Cite
|
Sign up to set email alerts
|

Genome‑wide analysis reveals the emerging roles of long non‑coding RNAs in cancer (Review)

Abstract: Cancer is the most intractable human disease that is primarily caused by genetic alterations. Recently, the general application of microarrays and high-throughput sequencing technology has revealed various important roles of long noncoding RNAs (lncRNAs) in cancer. This review summarizes the function, mechanism, diagnostic and treatment potential of lncRNAs identified through genome-wide analysis in cancer. Cell-, tissue-and development stage-specific expression patterns are major characteristics of cancer-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) exert an essential role in the occurrence and progression of tumors [3,4], mainly in cancer proliferation, metastasis, and other biological functions associated with tumorigenesis [5,6]. In PC, abnormal expression and dysfunction of lncRNAs are shown to be associated with rapid progression of cancer and distant metastasis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) exert an essential role in the occurrence and progression of tumors [3,4], mainly in cancer proliferation, metastasis, and other biological functions associated with tumorigenesis [5,6]. In PC, abnormal expression and dysfunction of lncRNAs are shown to be associated with rapid progression of cancer and distant metastasis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Small ncRNAs that regulate mRNAs can be predicted by numerous in-silico computational programs [ 21 , 22 ]. Long non-coding RNAs (lncRNAs) are another type of ncRNAs which are expressed in tissue-specific pattern and dysregulated in cancer [ 23 ] and play important functions in cellular processes such as cell proliferation, motility, and apoptosis [ 24 ]. Some reports have demonstrated that the levels of some lncRNAs, miRNAs and mRNAs are controlled and regulated by each other in cancer [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The differentially expressed lncRNAs have been revealed to be closely related to genesis and progression of various human cancer types. 13,14 Increasing literature has identified lncRNAs as crucial contributors in regulating the malignant characteristic of NSCLC through executing oncogenic or anti-oncogenic activities. [15][16][17] microRNAs (miRNAs) belong to a group of noncoding RNA transcripts, which are 17-24 nucleotides.…”
Section: Introductionmentioning
confidence: 99%